2017
DOI: 10.1002/14651858.cd008759.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count, spleen length, and platelet count-to-spleen length ratio for the diagnosis of oesophageal varices in people with chronic liver disease or portal vein thrombosis

Abstract: Platelet count, spleen length, and platelet count-to-spleen length ratio for the diagnosis of oesophageal varices in people with chronic liver disease or portal vein thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 126 publications
6
41
0
8
Order By: Relevance
“…One of the major limitations of these criteria, however, is their inapplicability when liver stiffness cannot be assessed for technical reasons, or when its measurement is unreliable, figures that in large cohorts of patients are observed in 3.1% and 15.8% of examinations, respectively, and that may jeopardise its accuracy when—due to these limitations—stiffness measurement cannot be applied to the whole population under evaluation 26,27 . On the other hand, the PLT/SDR has been validated in several, independent series of patients within a wide spectrum of disease severity and aetiology globally, and its diagnostic accuracy has been supported by at least two meta‐analyses, a systematic review and a Cochrane collaboration technical review 28‐37 …”
Section: Discussionmentioning
confidence: 99%
“…One of the major limitations of these criteria, however, is their inapplicability when liver stiffness cannot be assessed for technical reasons, or when its measurement is unreliable, figures that in large cohorts of patients are observed in 3.1% and 15.8% of examinations, respectively, and that may jeopardise its accuracy when—due to these limitations—stiffness measurement cannot be applied to the whole population under evaluation 26,27 . On the other hand, the PLT/SDR has been validated in several, independent series of patients within a wide spectrum of disease severity and aetiology globally, and its diagnostic accuracy has been supported by at least two meta‐analyses, a systematic review and a Cochrane collaboration technical review 28‐37 …”
Section: Discussionmentioning
confidence: 99%
“…Utilisation of better technologies to stratify for cirrhosis and OV including non‐invasive markers and MRI may have a future role . More recently non‐invasive tools such as Baveno criteria, liver stiffness to spleen/platelet score and platelet‐spleen ratio score have been validated as good negative markers to predict the absence of OV. Such non‐invasive tests may help minimise the subjective nature of human classification systems and reduce the overall work‐load of variceal screening endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not there is a 'glass ceiling' with subjective human classification systems, ie possibly no classification system will im- and platelet-spleen ratio score 24 have been validated as good negative markers to predict the absence of OV. Such non-invasive tests may help minimise the subjective nature of human classification systems and reduce the overall work-load of variceal screening endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…These scoring systems rely on a combination of platelet count, liver enzymes, albumin, and spleen size. A 2017 review states that the platelet count–to‐spleen ratio is the most accurate predictor in adults . In pediatric patients, the British Society of Paedatric Gastroenterology, Hepatology, and Nutrition endorsed that a platelet count of <120 × 10 9 /L should lead to surveillance .…”
Section: Diagnosis Management and Treatment Of Liver Disease In Cfmentioning
confidence: 99%
“…A 2017 review states that the platelet count-to-spleen ratio is the most accurate predictor in adults. (37) In pediatric patients, the British Society of Paedatric Gastroenterology, Hepatology, and Nutrition endorsed that a platelet count of <120 × 10 9 /L should lead to surveillance. (38,39) More recent studies using transient elastography have also demonstrated accuracy in identifying those individuals at greatest risk for portal hypertension.…”
Section: Cirrhosis and Portal Hypertensionmentioning
confidence: 99%